Mechanical Properties and Deformation Mechanisms of Heterostructured High-Entropy and Medium-Entropy Alloys: A Review - Jiang, Wei; Zhu, Yuntian; Zhao, Yonghao (Frontiers in Materials, 2022)
Recently, heterostructured (HS) materials, consisting of hard and soft zones with dramatically different strength, have been developed and received extensive attention because they have been reported to exhibit superior mechanical properties over those predicted by the rule of mixtures. Due to the accumulation of geometrically necessary dislocations during plastic deformation, a back-stress is developed in the soft zones to increase the yield strength of HS materials, which also induce forward stress in the hard zones and a global hetero-deformation induced (HDI) hardening to retain ductility. High-entropy alloys (HEAs) and medium-entropy alloys (MEAs) or multi-component alloys usually contain three or more principal elements in near-equal atomic ratios and have been widely studied in the world. This review paper first introduces concepts of HS materials and HEAs/MEAs, respectively, and then reviewed emphatically the mechanical properties and deformation mechanisms of HS HEAs/MEAs. Finally, we discuss the prospect for industrial applications of the HS HEAs and MEAs.